Needs Study of Interactive Flipbook of Local Wisdom for Reading Skills of Observation Report Text - Iflah Liidaini; Afnita; Dadi Satria (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the needs for developing an interactive flipbook incorporating local wisdom to enhance the observation report reading skills of eighth-grade students at SMP Negeri 40 Padang. The background of this research is based on students’ low interest in reading and limited ability to comprehend the content of observation report texts, caused by the lack of engaging, interactive, and contextual learning media. As a result, the Indonesian Language learning objectives in the Merdeka Curriculum have not been optimally achieved. This study employs a mixed methods approach, with the research design referring to the Analyze stage in the ADDIE development model. Data were collected through observations, interviews, questionnaires distributed to teachers and students, and curriculum document analysis. The subjects of the study included Indonesian Language teachers and eighth-grade students at SMP Negeri 40 Padang. Quantitative data were analyzed using descriptive percentage analysis, while qualitative data were examined through data reduction, data presentation, and conclusion drawing stages. The results indicate that both teachers and students have a high need for the development of digital learning media in the form of interactive flipbooks that align with student characteristics and local cultural values. Student needs analysis showed an average score of 79.05%, categorized as high, indicating students’ enthusiasm for visually engaging and easily understandable digital learning media. Furthermore, curriculum analysis revealed a gap between the learning outcomes of the Merdeka Curriculum and the actual classroom conditions, which are still dominated by conventional teaching materials. Therefore, an interactive flipbook based on local wisdom is considered relevant and promising to be developed as a learning medium capable of enhancing students’ learning motivation, reading interest, and meaningful comprehension of observation report texts.